PENGARUH PENERAPAN MODEL COOPERATIVE LEARNING TIPE TIME TOKEN BERBANTUAN MEDIA BENDA KONKRET TERHADAP PENGUASAAN VOCABULARY DI SEKOLAH DASAR - Dinda Galuh Suparmina, - (2020)
Vocabulary adalah kumpulan kata-kata beserta artinya dalam bahasa asing yang dipahami oleh seseorang ataupun kelompok. Semakin banyak vocabulary yang dikuasai maka pembelajar akan dapat membaca, berbicara, dan menulis tanpa mengalami hambatan. Sedangkan Time Token adalah salah satu pembelajaran kooperatif. Peserta didik dibentuk ke dalam kelompok belajar, yang mengajarkan keterampilan sosial untuk menghindari siswa mendominasi pembicaraan atau menghindarkan siswa diam sama sekali dalam berdiskusi. Penelitian ini bertujuan untuk mengetahui 1) penguasaan vocabulary siswa sebelum penerapan Model Cooperative Learning tipe Time Token berbantuan media benda konkret, 2) penguasaan vocabulary siswa sesudah penerapan Model Cooperative Learning tipe Time Token berbantuan media benda konkret, dan 3) pengaruh penerapan Model Cooperative Learning tipe Time Token berbantuan media benda konkret terhadap penguasaan vocabulary siswa SD kelas V. Penelitian jenis Pre-eksperimen One Group Pre-test Post-test dengan Subjek Tunggal yang berjumlah empat orang siswa kelas V SD dan bermukim di sekitar rumah peneliti. Hasil penelitian menunjukkan bahwa penerapan Model Cooperative Learning tipe Time Token berbantuan media benda konkret dapat meningkatkan penguasaan vocabulary siswa SD. Penguasaan vocabulary subjek termasuk ke dalam kategori cukup dengan rata-rata skor 79.06 dari hasil pretest. Dan dari hasil posttest, penguasaan vocabulary subjek termasuk ke dalam kategori sangat baik dengan rata-rata skor 93.75. Hasil analisis regresi linear sederhana menyatakan jika Model Cooperative Learning tipe Time Token berbantuan media benda konkret berkorelasi tinggi dengan penguasaan vocabulary sebesar 0.887. Didapatkan pula hasil koefisien determinasi pada kedua variabel sebesar 0.787 yang berarti 78% penguasaan vocabulary subjek dipengaruhi oleh Model Cooperative Learning tipe Time Token berbantuan media benda konkret. Vocabulary is a collection of words and their meanings in a foreign language understood by a person or group. The more vocabulary that is mastered, the learner will be able to understand reading, speaking, and writing without experiencing obstacles. Whereas Time Token is one of cooperative learning. Students are formed into study groups, this learning teaches social skills to avoid students dominating the conversation or avoiding students' silence altogether in discussions. This study aims to determine 1) the mastery of student vocabulary before the application of the Cooperative Learning Model of Time Token type assisted by concrete objects media, 2) the mastery of student vocabulary after applying the Cooperative Learning Model of Time Token type assisted by concrete object media, and 3) the effect of applying Cooperative Learning Model Time Token type assisted by concrete media objects to the mastery of vocabulary in grade 5 elementary school students. This type of research is the Pre-Experiment One Group Pre-test Post-test with a Single Subject. Subjects were four students in grade V elementary school and settled around the researcher's house. The results showed that the application of the Cooperative Learning Model Time Token type assisted by concrete media objects can improve the vocabulary mastery of elementary school students. Can be seen from the increase in the results of the pretest with the posttest. From the results of the pretest, mastery of the subject vocabulary included in the category enough with an average score of 79.06. While from the posttest results, mastery of vocabulary subjects included in the category very good with an average score of 93.75. Results of linear regression analysis state that if the Model Cooperative Learning Time Token-assisted by concrete object media high correlated with the mastery of vocabulary by 0.887 based on the classification of the correlation coefficient Guilford. Also, the results of the coefficient of determination on both variables amounted to 0.787 and has a meaning if 78% mastery of vocabulary subjects is influenced by the Cooperative Learning Model Time Token type aided by concrete media objects.